CO2-SR Cyclic Technology: CO2 Storage and in situ Regeneration with CH4 over a new dual function NiBa unsupported catalyst - Molina-Ramírez, Sergio; Cortés-Reyes, Marina; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; Alemany-Arrebola, Luis José (Elsevier, 2020)
A Ni-Ba unsupported catalyst has been developed to be used as a dual function material (DFM) for a new CO2 storage and in-situ regeneration (CO2-SR technology), consisting in a CO2 storage step followed by a CH4 regeneration phase, working in alternating, cyclic and isothermal regime. The heterometallic mixed-oxide catalyst-NiO.BaO- used in this technology was prepared by an ultrasonic assisted coprecipitation using 1:1 atomic ratio (Ni:Ba) and colloidal silica as an agent promoting surface area and improving mechanical properties. The solid obtained maintains the fcc-structure at higher temperatures, demonstrates high reducibility as a bulky catalyst and presents a connected and balanced strong basic sites and CH4 activation centres. It showed a CO2-storage net capacity of 0.232 mmolCO2g−1 and a CO2 and CH4 removal rate of 13.97 % and 11.04 % respectively, with a remarkable selectivity to hydrogen as an enriched-synthesis gas (H2+CO) stream at 600°C.
Keywords: Catalizadores; Syngas production; CO2-SR technology; NiBa unsupported catalyst; CO2-Storage CH4-Regeneration; Dual function material